Relationship between vigorous physical activity and health care costs among adolescents: ABCD Growth Study - Wésley Torres; Lucas Gabriel de Moraes Chagas; Rômulo Araújo Fernandes; Monique Yndawe Castanho Araujo; Jacqueline Bexiga Urban; Santiago Maillane-Vanegas; Bruna Camilo Turi-Lynch; Jamile Sanches Codogno; Nana Kwame Anokye (BMC, 2022)
Abstract Background The relationship between physical activity and health care costs among adolescents is not yet clear in the literature. Objective To analyze the relationship between physical activity and annual health care costs among adolescents. Methods The present sample was composed of 85 adolescents of both sexes with ages ranging from 11 to 18 years (mean age 15.6 ± 2.1). Health care costs were self-reported every month for 12 months, and information on health care values was verified with local pharmacies, private health care plans, and the National Health Service. The time spent in different physical activity intensities was objectively measured by accelerometers. Confounding variables were: sex, age, somatic maturation, body fatness, blood pressure, and components of dyslipidemia and insulin resistance. Multivariate models were generated using generalized linear models with gamma distribution and a log-link function. Results The overall annual health care cost was US$ 733.60/ R$ 2,342.38 (medication: US$ 400.46 / R$ 1,278.66; primary and secondary care: US$ 333.14 / R$ 1,063.70). The time spent in vigorous physical activity (minutes/day) was negatively related to health care costs (r = -0.342 [95% CI: -0.537,-0.139]; β = -0.06 cents (95% CI: -0.089, -0.031). Conclusion Vigorous physical activity seems to be associated with lower health care costs among adolescents.